Pitch angle control of a grid connected wind turbine - Ahmed, S.a; Yaakob, S.B.a; Yusof, A.a (2014)
The focus of this paper is to design an active control system that can regulate pitch angle (angle at which blade rotates around its own axis) of the turbine blade. It will vary the mechanical torque input to the generator of a wind energy conversion system and in turn control the power extracted from the wind at a particular wind speed. A small change in pitch has effect on the extraction of available energy, reduction of torque and output power variation to the grid. In this paper a fuzzy-Pl control system is modeled and the oscillation in grid power due to change in pitch position is analyzed. Furthermore it is shown that fuzzy-Pl offers limited output power oscillation when compared to conventional Pl controller.